Income per-capita across-countries: Stories of catching-up, stagnation, and laggardness - Juan Ricardo Perilla (Journal of Applied Economics, 2024)
The convergence/divergence debate and plausible explanations to the process of catching-up remain highly controversial research areas in growth economics. Recently, these issues have been the subject of questionable predictions with regard future prospect for backward countries, raising concerns about the right direction of macroeconomic policy. To explore these issues, a sample of 131 countries is studied over the 1950s-2010s to identify those that have managed to catching-up, remain stagnant, or keep lagging further behind. Time-distance to the frontier and productivity decompositions, based on non-parametric methods, suggest that some countries have successfully completed already the caching-up, and it would take between 27 and 194 years for others to do so in the most optimistic scenario. But many others would never do. Policy implications drawn from the comparative analysis suggests the need to strengthen local innovation in order to increase the ability to catching-up alongside widespread reliance on technology diffusion from abroad.
Keywords: 330; convergence; Economic development and economic growth; innovation; technology diffusion